Adolescents and young adults (AYA) with acute myeloid leukemia (AML): real-world long-term results and age-specific outcomes. Issue 13 (10th November 2022) - Lalayanni, Chrysavgi; Demosthenous, Christos; Iskas, Michail; Kelaidi, Charikleia; Papathanasiou, Maria; Syrigou, Antonia; Athanasiadou, Anastasia; Papalexandri, Apostolia; Batsis, Ioannis; Vardi, Anna; Polychronopoulou, Sophia; Sakellari, Ioanna
Abstract: Opposing acute lymphoblastic leukemia, sparse data about AYAs with acute myeloid leukemia (AML) is available. Overall, 125 AYAs (age 10–35 years) treated during the last two decades were evaluated and compared to 385 older patients. CBF leukemia was more frequent in AYAs (21.6% vs. 8%, p  < 0.001); however, many presented high-risk features. AYAs showed improved complete remission rate (CR, 80% vs. 65%, p  = 0.01), lower cumulative incidence of relapse and TRM and longer survival (5 year-OS 53% vs. 24%, p  < 0.0001), observed mainly in intermediate-risk karyotype. Adolescents displayed even better outcomes (5 year-OS 69%). AlloHCT in CR1 was beneficial for nonadolescent AYAs (5 year-OS 66.7% vs. 44.4% without HCT, p  = 0.04). Among 50 APL patients, 19 AYAs experienced better outcomes than older, mainly attributed to reduced treatment-related mortality (TRM, 5% vs. 19%, p  = 0.1). We observed an important (>10%) survival gain for AYAs during the last decade. However, AYAs have still unmet needs to obtain optimal cure rates.